2019
DOI: 10.2196/12536
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Medicine in Patients With Breast Cancer: Exploratory Study of Social Network Forum Data

Abstract: BackgroundPatients and health care professionals are becoming increasingly preoccupied in complementary and alternative medicine (CAM) that can also be called nonpharmacological interventions (NPIs). In just a few years, this supportive care has gone from solutions aimed at improving the quality of life to solutions intended to reduce symptoms, supplement oncological treatments, and prevent recurrences. Digital social networks are a major vector for disseminating these practices that are not always disclosed t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 39 publications
1
33
0
1
Order By: Relevance
“…The presented study shows that a significant number of patients using unconventional practices gave up on standard procedures of oncological treatment, while some patients were considering giving up this treatment in the future. It seems to be crucial to apply proper methods of communication with these patients, which should be based on EBM and effective communication skills [33,34]. The majority of the respondents confirmed improvement after administration of unconventional therapies, which is consistent with prior literature analysis [25].…”
Section: Discussionsupporting
confidence: 78%
“…The presented study shows that a significant number of patients using unconventional practices gave up on standard procedures of oncological treatment, while some patients were considering giving up this treatment in the future. It seems to be crucial to apply proper methods of communication with these patients, which should be based on EBM and effective communication skills [33,34]. The majority of the respondents confirmed improvement after administration of unconventional therapies, which is consistent with prior literature analysis [25].…”
Section: Discussionsupporting
confidence: 78%
“…General health information refers to common medical and health information, which is usually open to the public and can be easily obtained by the masses, such as information on doctors and hospitals, prices of medicines, and features of a specific disease. Special health information is usually concerned with privacy, which refers to personal empirical information, including medical records, treatment, and personal health conditions [15].…”
Section: Information-sharing Behaviors In Online Patient Communitiesmentioning
confidence: 99%
“…Numerous studies discussed how social media acts as a vehicle for the spread of misinformation about CAM [34,35,42,47,48,53]. For example, since the onset of the COVID-19 pandemic, the amount and popularity of tweets suggesting a link between spinal manipulation therapy (SMT) and immunity increased substantially [34].…”
Section: Theme 2: Misinformation About Cam On Social Mediamentioning
confidence: 99%
“…Furthermore, posts about CAM on breast cancer patient social forums and Facebook groups have raised critical concerns about the reliability of information accessible to patients [42]. For example, it was found that some patients test CAM therapies that have not yet been proven or whose manufacturing quality have not been veri ed [42]. Additionally, information that is potentially dangerous can be shared on social media and avoid review from regulatory and monitoring systems [42].…”
Section: Theme 2: Misinformation About Cam On Social Mediamentioning
confidence: 99%